2003
DOI: 10.1590/s0101-20612003000400006
|View full text |Cite
|
Sign up to set email alerts
|

Pós-colheita de pêssegos (Prunus pérsica L. Bastsch) revestidos com filmes a base de amido como alternativa à cera comercial

Abstract: O pessegueiro (Prunus persica L. Bastsch) é uma planta da família das rosáceas, originaria da Ásia. Dos frutos de clima temperado, o pêssego é um dos mais perecíveis, em razão do seu rápido metabolismo após a colheita. A aplicação de ceras começou a ser estudada na década de 80. Apesar de se mostrar eficiente, tem como principal limitação seu custo e o possível efeito residual nos frutos. O uso da cobertura de cera para pêssegos estende-lhes a vida de mercado pela redução na perda de umidade e, conseqüentement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 3 publications
0
6
0
19
Order By: Relevance
“…Turbidity and syneresis analyses of starch gel were performed according to Oliveira & Cereda (2003). A suspension of 8% starch in water was heated to obtain a translucent gel, which was distributed into five containers of 100 ml (approximately 20 ml of gel per container), cooled and stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Turbidity and syneresis analyses of starch gel were performed according to Oliveira & Cereda (2003). A suspension of 8% starch in water was heated to obtain a translucent gel, which was distributed into five containers of 100 ml (approximately 20 ml of gel per container), cooled and stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Maftoonazad et al (2008) [9] found that the shelf life of pieces of peach could be extended using sodium alginate and methyl cellulose coatings. Different studies [12,13] focused on edible coatings on whole fruit of nectarine and peach. Pizato et al (2013) [14] applied different coatings to cubes of peach.…”
Section: Introductionmentioning
confidence: 99%
“…A fécula gelatinizada que se obtém, quando resfriada, forma películas devido às suas propriedades de retrogradação. Na retrogradação, pontes de hidrogênio são formadas e o material disperso volta a se organizar em macromoléculas, originando uma película (OLIVEIRA, 2000).…”
Section: Introductionunclassified